Meningkatkan Hasil Belajar Matematika Materi Pengukuran Panjang Melalui Penerapan Model Problem Based Learning Di Kelas II SD YPPK Iwaka Mimika - Elisabeth Moi (Lembaga Pengembangan Kinerja Dosen, 2021)
This research aims to determine the results of learning Mathematics in Length Measurement Material using the Problem Based Learning Model in class II students at SD YPPK Iwaka Mimika. The research subjects were class II students with a total of 20 people. The instrument used was to collect data in this research using observation tests. The test used is descriptive. Student learning outcomes in cycle I when implementing the Problem Based Learning learning model obtained an average of 72.0 with a completion percentage of 85% after the teacher reflected and corrected several deficiencies so that student learning outcomes in cycle II increased to 100% with an average score of 81. .0 with the highest score of 100 obtained by 2 people and the lowest 70 obtained by 5 people who have achieved the standard of learning completeness. It was concluded that using the Problem Based Learning Model can improve Mathematics Learning Outcomes on the main material of Length Measurement in class II of SD YPPK Iwaka Timika.